Comprehensive Review of Multidetector Computed Tomography (MDCT) in the Assessment of Blunt Cervical Spine Trauma in Adults - Akash Kumbhalkar; Nikhita Dhange; Neha Nawale; Sanket Mahajan (Journal of Pharmacy and Bioallied Sciences)
Since the release of 64-section computed tomographic (CT) scanners in 2004, there have been several new advancements in cervical spine imaging. A growing trend in polytrauma patients with obtain-dating is the use of multidetector CT as a stand-alone screening test to rule out cervical injuries. Spine surgeons are beginning to adopt the SLIC (Subaxial Injury Classification and Scoring) method for the cervical spine based on CT and MR imaging data. Multidetector CT is currently being used to reassess radiographic parameters that were previously established for the evaluation of craniocervical distraction injuries. Even while most blunt trauma patients are presently managed without surgery, procedures for management have changed to favor surgical intervention because of improved surgical techniques, hardware, and breakthroughs in our understanding of spinal stability. For this reason, radiologists need to be aware of this. Cervical spine imaging has significantly improved since the introduction of 64-section computed tomography (CT) scanners in 2004. MDCT has become a single imaging modality of significance in the evaluation of polytrauma patients, especially those who are obtunded to assess for cervical spine injury. The recent generation of Subaxial Injury Classification and Scoring (SLIC) based on CT and MRI is establishing itself among spine surgeons. Regarding craniocervical distraction injuries, the role of MDCT is also being rediscussed. Cervical spine injuries that are found in 5–10% of the cases of blunt trauma affect the spinal cord and require more demanding investigations because of a high rate of noncontiguous lesions. MDCT is increasingly used in cervical spine clearance because of the higher sensitivity compared with radiography in patients with other injuries that distract the cervical spine. Cervical spine CT is recommended in these cases by the American College of Radiology. The superiority of MR imaging in identifying disc and ligament abnormalities is counterbalanced by the higher false-positive study rates and modest effect on management; for this reason, MDCT remains preferable for screening purposes. CD as a form of ligamentous injury with neurological deficit as its component signifies the value of an MDCT scan in its early diagnosis. Occipital condyle injuries as a sign of high-tied trauma and atlas and axis fractures, highly stable and some of which require different treatment, also enable further improvement of MDCT detection. Current diagnostic imaging has replaced radiography mostly because of better visualization and sensitivity, especially among high-risk patient groups. In conclusion, MDCT can be advocated as the gold standard in the primary assessment of blunt cervical spine injury due to improved and sensitive diagnostic performance. At the same time, the radiation dose issue remains the current radiologist challenge.